Anthropometrical, physiological and psychological characteristics among competitive rowers - Alföldi, Z. (University of Pécs, 2023)
The overall purpose of the present Ph.D. dissertation is to advance Hungarian rowing. In order to achieve this goal useful performance prediction model should be established, which may help the talent identification for rowing at early ages. For this reason, the physical and psychological parameters that influence rowing performance must be examined. Thus, extensive data acquisition and the analysis of the collected information are required. The differences in the anthropometric and physiological as well as psychological profiles of Hungarian rowers in various ages, rankings and different genders were widely examined, aiming to find the answer for the following questions listed below, which could contribute to the development of a rowing performance prediction model. The following hypotheses were investigated in the dissertation: